2015
DOI: 10.1007/s11605-015-2857-5
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Versus Open Surgery for Mid-Low Rectal Cancer: a Systematic Review and Meta-Analysis on Short- and Long-Term Outcomes

Abstract: This study suggests that the safety and feasibility of laparoscopic surgery appear to be equivalent to open surgery for treatment of mid- low rectal cancer, with the more favourable short-term benefits, fewer complications, comparable pathological outcomes and long-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 63 publications
2
24
0
1
Order By: Relevance
“…In a comparison of the long-term outcomes after laparoscopic TME and open TME, similar local recurrence, distant metastasis, and tumor-free survival rates were found. 15 Considering the early period oncologic results of robotic TMEs in rectal cancers, both the laparoscopic and open TME are similar in this regard. 18 However, some researchers have reported that robotic surgery provides better outcomes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a comparison of the long-term outcomes after laparoscopic TME and open TME, similar local recurrence, distant metastasis, and tumor-free survival rates were found. 15 Considering the early period oncologic results of robotic TMEs in rectal cancers, both the laparoscopic and open TME are similar in this regard. 18 However, some researchers have reported that robotic surgery provides better outcomes.…”
Section: Discussionmentioning
confidence: 96%
“… 13 , 14 As such, laparoscopic TME is performed increasingly, because its benefits are not less than those of open surgery, especially in long-term oncologic outcomes. 15 Nevertheless, despite all the aforementioned advantages, laparoscopic TME is a difficult procedure, even for experienced surgeons. For this reason, laparoscopic TME is still the less frequently preferred option worldwide, as opposed to an open TME for rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent meta-analysis for long-term survival focused on relative risks showed a similar result for overall survival and disease-free survival (RR = 1.06, 95 % CI 0.96–1.18, I 2 = 14 %; RR = 1.04, 95 % CI 0.95–1.14, I 2 = 0 %) in 4 studies with 847 patients [ 23 ]. Though there are some other meta-analysis focus on this topic [ 24 , 25 ], odds ratios and continuous variables were presented in the form of weighted mean differences with 95 % credible intervals. In systematic reviews and meta-analysis, time-to-event outcomes are most appropriately analyzed using hazard ratios.…”
Section: Discussionmentioning
confidence: 99%
“…To date, routine use of laparoscopic over open LAR for rectal cancer is not established in international guidelines. Despite high‐quality surgery, large robust randomized trials and meta‐analyses did not show non‐inferior oncologic outcomes for laparoscopic LAR . It is our opinion that the LA approach may bridge this gap between TL and open surgery in managing the entire range of rectal cancer presentations, without compromising on oncological outcomes.…”
Section: Discussionmentioning
confidence: 92%